A Mixed-Methods Analysis of Critical Thinking Skills and Contributing Factors: The Case of Indonesian Pre-service Biology Teachers - Astutik, Fuji; Ruswan, Ruswan; Mindiana, Agnes Tasya; Wijayanti, Erna (Jurnal Pendidikan MIPA, 2025)
The purpose of this study was to measure the critical thinking skills of student teachers and the factors influencing them. The survey involved 477 participants from an Islamic university, including six lecturers. Data were collected in three stages. The level of critical thinking skills was measured using a test whose items were developed based on the Watson-Glaser Critical Thinking Appraisal (WGCTA) indicators. The study also reviewed lesson plans, student worksheets, and cognitive test questions. Interviews were conducted with four students from each year, the highest- and lowest-skilled, as well as with six lecturers. A one-way ANOVA was used to examine differences in critical thinking skills across university study lengths. Qualitative data were analyzed using content analysis methods. The study's findings indicated that four groups had critical thinking skills in the "moderate" category and showed no significant differences among themselves (p = 0.215 > 0.05). The ANOVA was performed separately for each indicator to identify any that differed significantly. The results indicate that the indicators of interpretation (0.02 < 0.05) and argument evaluation (0.041 < 0.05) differ significantly among groups. There was a significant difference in the interpretation indicator between freshmen and junior students. Meanwhile, there was a significant difference between freshmen (the highest average) and sophomores in terms of argument evaluation. Student learning experiences, including the use of learning models, assignments, student worksheets, and evaluation questions (learning assessments), were the main factors influencing critical thinking skills. As a potential step toward developing critical thinking skills, students are expected to read, review, and complete assignments independently. Study programs can evaluate curricula that emphasize critical thinking skills.   Keywords: contributed factor, critical thinking skills, pre-service biology teachers.